POLA PENDIDIKAN KARAKTERBERBASISAGAMADI SMK ISLAMIC CENTER PALU KELURAHAN PETOBO KECAMATAN PALU SELATAN - A. Markarma (ISTIQRA, 2016)
From the spirit of forming a nation's character, character education emerging ideas that must be developed among dihonest, discipline, tolerance, and love of the homeland. This is where many of the concepts and patterns of character education is offered including religious based character education pattern. In this context, researchers wanted to examine further how the pattern of religious based character education in Palu Islamic Center vocational school. This research is quantitative descriptive. Researcher used statistical-based quantitative analysis. The sampling method using Slovin formula. The study design was made for the implementation of the research can be executed properly. While the research instruments are arranged to direct the implementation of research activities. The results showed that the pattern of religious based character education in in Palu Islamic Center vocational school, are not included in a subject, but is integrated in subjects. Teachers integrate values-based character of religion in the curriculum religious based character education curriculum in in Palu Islamic Center vocational school, conducted integrally teachers on the subjects and the results are effectively shaping the attitudes and behavior of students. The implication can improve students' understanding of religion. Students can understand the values ​​of Islam in all fields studied. Character is built to form attitude and good student behavior and entrenched in daily life